Why do parasites exhibit reverse latitudinal diversity gradients? Testing the roles of host diversity, habitat and climate. Issue 9 (28th June 2021) - Johnson, Pieter; Haas, Sarah E.
Abstract: Aim: The latitudinal diversity gradient (LDG), in which species richness decreases from the equator towards the poles, is among the most fundamental distributional patterns in ecology. Despite the expectation that the diversity of parasites tracks that of their hosts, available evidence suggests that many parasites exhibit reverse latitudinal gradients or no pattern, yet the rarity of large‐scale datasets on host–parasite interactions calls into question the robustness of such trends. Here, we collected parasitological data from a host group of conservation importance, lentic‐breeding amphibians, to characterize the form and direction of relationships among latitude, parasite richness and parasite load. Location: The contiguous USA. Time period: 2000–2014. Major taxa studied: Lentic‐breeding frogs and toads and their helminth parasites. Methods: We collected information on parasite richness and infection load for 846 amphibian populations representing 31 species. We combined these data with environmental and biological data to test for LDGs and potential mechanisms. Results: Both parasite richness and parasite abundance increased across 20° of latitude (i.e., a reverse LDG). For parasite richness, this pattern was explained, in part, by latitudinal increases in wetland area, land‐cover diversity and the richness of waterbirds, which function as definitive hosts for many amphibian parasites. Host body size also correlated positively with latitude and helminth richness, potentially reflecting increased habitat availability, greater host longevity or a persistent phylogenetic signal. Parasite abundance associated positively with wetland area and land‐cover diversity, but negatively with amphibian taxonomic richness. Longitude exhibited nonlinear relationships with parasite abundance and richness, which we suggest stem from large‐scale variation in host availability (e.g., migratory bird flyways). Main conclusions: With growing interest in the distribution of parasites and pathogens, these results highlight the importance of inverse latitudinal gradients while emphasizing the explanatory influence of host body size, habitat availability and host diversity.